ChemInform Abstract: Birch Reductive Alkylation of Methyl m‐(Hydroxymethyl)benzoate Derivatives and the Behavior of o‐ and p‐(Hydroxymethyl)benzoates under Reductive Alkylation Conditions. Issue 20 (25th April 2013) - Fretz, Samuel J.; Hadad, Christopher M.; Hart, David J.; Vyas, Shubham; Yang, Dexi
Abstract Title reaction of methyl m‐(hydroxymethyl)benzoate derivatives using lithium in ammonia/THF in the presence of tert‐butyl alcohol, is achieved without loss of benzylic oxygen substituents.